2001
DOI: 10.1046/j.1365-2389.2001.00412.x
|View full text |Cite
|
Sign up to set email alerts
|

Carbon sequestration in forest soils: effects of soil type, atmospheric CO2 enrichment, and N deposition

Abstract: Summary Soil contains the major part of carbon in terrestrial ecosystems, but the response of this carbon to enriching the atmosphere in CO2 and to increased N deposition is not completely understood. We studied the effects of CO2 concentrations at 370 and 570 μmol CO2 mol−1 air and increased N deposition (7 against 0.7 g N m−2 year−1) on the dynamics of soil organic C in two types of forest soil in model ecosystems with spruce and beech established in large open‐top chambers containing an acidic loam and a ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
31
0
1

Year Published

2006
2006
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(38 citation statements)
references
References 34 publications
6
31
0
1
Order By: Relevance
“…The nutrients are largely interlinked and influenced by other physico-chemical characters of the soil, depending on seasonal changes [40]. Yankelevich et al [34] predicted that if each tree species generates a particular soil environment under its canopy, then under a diverse tree community, soil chemical properties will be spatially very heterogeneous.…”
Section: Physico-chemical Propertiesmentioning
confidence: 99%
“…The nutrients are largely interlinked and influenced by other physico-chemical characters of the soil, depending on seasonal changes [40]. Yankelevich et al [34] predicted that if each tree species generates a particular soil environment under its canopy, then under a diverse tree community, soil chemical properties will be spatially very heterogeneous.…”
Section: Physico-chemical Propertiesmentioning
confidence: 99%
“…On the other hand, an increase in standing volume under the biodiversity scenario keeps NO 3 − concentrations low in three of the four model regions. In DH, the high N deposition and N release from soils with high organic matter stocks may not be compensated by the N uptake of the forest stands Several studies showed that the C sequestration rate of forest soils is increased under elevated N deposition [99][100][101], however, the efficiency of this effect differs considerably [102,103]. It may to some extent be accounted for in the VSD+ simulations where the foliar N content is dependent on N deposition.…”
Section: Trends In Soil Organic Mattermentioning
confidence: 99%
“…where K m is the affinity constant for CO 2 The original C-Fix does not include a specific index which accounts for the possible short-term effect of water stress on photosynthesis, as is done by other Monteith type models [e.g., 5,23]. The need to apply C-Fix also in Mediterranean environments, that are characterized by a long summer dry season during which vegetation growth is limited by water availability [24], induced Maselli et al [25] to include such an additional water stress index.…”
Section: Application Of C-fix To Present Environmental Conditionsmentioning
confidence: 99%
“…Among them, forest ecosystems cover about 40% of the Earth's ice-free land surface and represent a great part of the global carbon stock [1,2], which must be quantified also in view of the carbon emission trading by countries [3]. Worldwide forests account for about 75% of the carbon stored in terrestrial ecosystems (organic carbon, OC) and approximately 40% of the carbon exchange between the atmosphere and the terrestrial biosphere each year [4].…”
Section: Introductionmentioning
confidence: 99%